Safety and efficacy of opicinumab in acute optic neuritis (RENEW): a randomised, placebo-controlled, phase 2 trial - Cadavid, Diego; Balcer, Laura; Galetta, Steven; Aktas, Orhan; Ziemssen, Tjalf; Vanopdenbosch, Ludo; Frederiksen, Jette; Skeen, Mark; Jaffe, Glenn J; Butzkueven, Helmut; Ziemssen, Focke; Massacesi, Luca; et al. (Lancet neurology, 2017)
The human monoclonal antibody opicinumab (BIIB033, anti-LINGO-1) has shown remyelinating activity in preclinical studies. We therefore assessed the safety and tolerability, and efficacy of opicinumab given soon after a first acute optic neuritis episode. This randomised, double-blind, placebo-controlled, phase 2 study (RENEW) was done at 33 sites in Australia, Canada, and Europe in participants (aged 18–55 years) with a first unilateral acute optic neuritis episode within 28 days from study baseline. After treatment with high-dose methylprednisolone (1 g/day, intravenously, for 3–5 days), participants were assigned with a computer-generated sequence with permuted block randomisation (1:1) using a centralised interactive voice and web response system to receive 100 mg/kg opicinumab intravenously or placebo once every 4 weeks (six doses) and followed up to week 32. All study participants and all study staff, including the central readers, were masked to treatment assignment apart from the pharmacist responsible for preparing the study treatments and the pharmacy monitor at each site. The primary endpoint was remyelination at 24 weeks, measured as recovery of affected optic nerve conduction latency using full-field visual evoked potential (FF-VEP) versus the unaffected fellow eye at baseline. Analysis was by intention-to-treat (ITT); prespecified per-protocol (PP) analyses were also done. This study is registered with ClinicalTrials.gov, number NCT01721161. The study was done between Dec 21, 2012, and Oct 21, 2014. 82 participants were enrolled, and 41 in each group comprised the ITT population; 33 participants received opicinumab and 36 received placebo in the PP population. Adjusted mean treatment difference of opicinumab versus placebo was −3·5 ms (17·3 vs 20·8 [95% CI −10·6 to 3·7]; 17%; p=0·33) in the ITT population, and −7·6 ms in the PP population (14·7 vs 22·2 [−15·1 to 0·0]; 34%; p=0·050) at week 24 and −6·1 ms (15·1 vs 21·2 [−12·7 to 0·5]; 29%; p=0·071) in the ITT population and −9·1 ms (13·2 vs 22·4 [−16·1 to −2·1]; 41%; p=0·011) in the PP population at week 32. The overall incidence (34 [83%] of 41 in each group) and severity of adverse events (two [5%] of 41 severe adverse events with placebo vs three [7%] of 41 with opicinumab) were similar between groups and no significant effects on brain MRI measures were noted in either group (mean T2 lesion volume change, 0·05 mL [SD 0·21] for placebo vs 0·20 mL [0·52] with opicinumab; 27 [77%] of 35 participants with no change in gadolinium-enhancing [Gd+] lesion number with opicinumab vs 27 [79%] of 34 with placebo; mean 0·4 [SD 0·79 for the placebo group and 0·85 for the opicinumab group] new Gd+ lesions per participant in both groups). Treatment-related serious adverse events were reported in three (7%) of 41 participants in the opicinumab group (hypersensitivity [n=2], asymptomatic increase in transaminase concentrations [n=1]) and none of the participants in the placebo group. Remyelination did not differ significantly between the opicinumab and placebo groups in the ITT population at week 24. However, results from the prespecified PP population suggest that enhancing remyelination in the human CNS with opicinumab might be possible and warrant further clinical investigation. Biogen.